6 + 2 < 9 + 3...u r correct
2<span>x<span><span></span></span></span>² <span><span><span> </span></span></span>+ 2x − 2<span>4
</span><span>GCF = 2
2(2x</span>²/2 + 2x/2 - 24/2)
<span>
2(x - 3)(x + 4)</span>
If I could get more context then that would help. Because an exponent being an odd number doesn’t do anything, so it could be either a negative or a positive
Answer: -4x(4x - 15)
Step-by-step explanation:
f(x) =
+ 60x
y =
+ 60x
=> - (
- 60x)
=> -4x(4x - 15)
Answer:
Step-by-step explanation:
Distribute: 6(4-z) expands to 24-6z
24-6z=2z: Add 6z to both sides to get 24=8z
Divide both sides by 8: z=3